The psychology of criminal and antisocial behavior : victim and offender perspectives - Petherick, Wayne; Sinnamon, Grant; Crime Victims (Amsterdam : Elsevier, Academic Press, 2017)
The psychology of criminal and antisocial behavior : victim and offender perspectives is not just another formulaic book on forensic psychology. Rather, it opens up new areas of enquiry to busy practitioners and academics alike, exploring topics using a practical approach to social deviance that is underpinned by frontier research findings, policy, and international trends. From the relationship between psychopathology and crime, and the characteristics of catathymia, compulsive homicide, sadistic violence, and homicide victimology, to adult sexual grooming, domestic violence, and honor killings, experts in the field provide insight into the areas of homicide, violent crime, and sexual predation. In all, more than 20 internationally recognized experts in their fields explore these and other topic, also including discussing youth offending, love scams, the psychology of hate, public threat assessment, querulence, stalking, arson, and cults. This edited work is an essential reference for academics and practitioners working in any capacity that intersects with offenders and victims of crime, public policy, and roles involving the assessment, mitigation, and investigation of criminal and antisocial behavior. It is particularly ideal for those working in criminology, psychology, law and law enforcement, public policy, and for social science students seeking to explore the nature and character of criminal social deviance--Back cover.
Psychopathology as a mediator of antisocial and criminal behavior -- Catathymia and compulsive homicide : a psychologyical perspective -- Victimology and predicting victims of personal violence -- Threat and violence intervention : influenced by victim and offender perspectives -- Profiling in violent crimes : the perpetrator and the victim in cases of filicide -- Risk assessment in youth justice : a child-centered approach to managing interventions -- Reciprocity and exchange : perspectives of male victims of family violence -- Stalking -- Stalking public figures : the fixated loner -- Circumscribing cyperbullying : toward a mutual definition and characterization of aggression, assault, and recklessness via telecommunications technology -- Domestic violence : psychological issues related to the victim and offender -- Honor killing and domestic violence : the same or different? -- Homicide in Australia -- Victims of child sexual abuse : the psychology of victims -- Child sexual offenders : the psychology of offending -- The psychology of adult sexual grooming : Sinnamon's seven-state model of adult sexual grooming -- Searching for the spectrum of the querulous -- A multidisciplinary apprach to understnading internet love scams : implications for law enforcement -- Firesetters : a review of theory, facts, and treament -- Cults.
Includes bibliographical references and index.
Keywords: The psychology of criminal and antisocial behavior : victim and offender perspectives is not just another formulaic book on forensic psychology. Rather, it opens up new areas of enquiry to busy practitioners and academics alike, exploring topics using a practical approach to social deviance that is underpinned by frontier research findings, policy, and international trends. From the relationship between psychopathology and crime, and the characteristics of catathymia, compulsive homicide, sadistic violence, and homicide victimology, to adult sexual grooming, domestic violence, and honor killings, experts in the field provide insight into the areas of homicide, violent crime, and sexual predation. In all, more than 20 internationally recognized experts in their fields explore these and other topic, also including discussing youth offending, love scams, the psychology of hate, public threat assessment, querulence, stalking, arson, and cults. This edited work is an essential reference for academics and practitioners working in any capacity that intersects with offenders and victims of crime, public policy, and roles involving the assessment, mitigation, and investigation of criminal and antisocial behavior. It is particularly ideal for those working in criminology, psychology, law and law enforcement, public policy, and for social science students seeking to explore the nature and character of criminal social deviance--Back cover; Criminal Behavior; Criminals